2018
DOI: 10.5688/ajpe6315
|View full text |Cite
|
Sign up to set email alerts
|

Student Learning with Generated and Answered Peer-written Questions

Abstract: To investigate the degree to which student-generated questions or answering student-generated multiple-choice questions predicts course performance in medicinal chemistry. Students enrolled in Medicinal Chemistry III over a 3-year period were asked to create at least one question per exam period using PeerWise; within the software, they were also asked to answer and rate one peer question per class session. Students' total reputation scores and its components (question authoring, answering, and rating) and tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
0
5
0
1
Order By: Relevance
“…Walsh et. al. demonstrated that students involved in question-writing performed significantly better on a subsequent institutional summative assessment, but did not control for baseline academic differences between those students who wrote MCQs and those who did not [8,9].These improvements in examination performance through involvement in MCQ-writing have also been shown in other healthcare professions training programs including nursing, pharmacy, and dentistry, but with similarly variable approaches ranging from associations between student ratings of peer-created MCQs and exam performance to true randomization with control group comparison [14][15][16].…”
Section: Introductionmentioning
confidence: 88%
“…Walsh et. al. demonstrated that students involved in question-writing performed significantly better on a subsequent institutional summative assessment, but did not control for baseline academic differences between those students who wrote MCQs and those who did not [8,9].These improvements in examination performance through involvement in MCQ-writing have also been shown in other healthcare professions training programs including nursing, pharmacy, and dentistry, but with similarly variable approaches ranging from associations between student ratings of peer-created MCQs and exam performance to true randomization with control group comparison [14][15][16].…”
Section: Introductionmentioning
confidence: 88%
“…Currently, literature which reports on deployments of the PeerWise software is disproportionately biased towards experiences from STEMM subjects (Biggins et al, 2015;Hancock et al, 2018;Harris, Walsh, Denny, & Smith, 2018;Hudson, Jarstfer, & Persky, 2018;Kay et al, 2018, Mac Raighne et al, 2015Rhodes, 2013) compared to discursive subjects (Humpage, 2014;Renzo, 2014). Accordingly, a primary aim of this paper was to assess whether the desirable outcomes associated with implementing student-authored MCQ software such as PeerWise (ie, engagement with course content and student satisfaction) reported in accounts from STEMM deployments (Biggins et al, 2015;Hancock et al, 2018;Mac Raighne et al, 2015;Tatachar & Kominski, 2017) may be replicable in discursive subjects, where course content is characterised by more nuance and interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…Estos hallazgos son acordes con los de estudios previos realizados con estudiantes de la misma universidad española en el Grado de Psicología (Morales et al, 2021) y de Medicina (Nso-Roca et al, 2020). También están en línea con estudios internacionales de universidades de diferentes países que apoyaron que el uso de PeerWise se relacionaba de forma positiva y significativa con el rendimiento académico general o en los exámenes tanto en el grado en Psicología (Howe et al, 2018) como en diversas titulaciones (e.g., Hancock et al, 2018;Hudson et al, 2018;Kay et al, 2020;McQueen et al, 2014). Por lo que, con los datos disponibles hasta la fecha, parece existir un sólido apoyo a la relación positiva entre el uso de PeerWise y el rendimiento académico entre estudiantes universitarios de diferentes universidades y disciplinas.…”
Section: Discusión Y Conclusionesunclassified